(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
The contribution presents the archaeological investigations made in the ancient town of Nora by University of Milan in the so-called area “delle case a mare”, and more exactly in the northern sector of this district, called sector A. First of all, starting from reading the original diaries of former superintendent Gennaro Pesce, who first, in Fifties, excavated this area, we want to illustrate the problems existing in “re-investigation” of an archaeological area inspected with different work’s methodologies; later, a general panoramic of examined rooms is shown, focusing on preliminary archaeological operations and on planimetric and architectonic aspects of the archaeological evidences.